Microstructure and mechanical properties of self-reinforced cross-linked polyurethanes based on oligobutadiene diol - Yakushev , R.M.; Yakusheva, D.E.; Astaf’eva, S.A. (Perm Federal Research Centre Journal, 2023)
Self-reinforced polyurethanes based on oligobutadiene diol have been synthesized by one- and twostage (prepolymer) technique. Some regularities of the hard phase (pseudofiller) formation have been studied by SEM. Breaking strength, modulus and relative elongation have been determined. Mechanical properties and pseudofiller particle size have been found to be dependent both on low molecular alcohol content and synthesis technique. Experimental data treatment by simplex method allowed the optimum composition area to be revealed.